Adubação nitrogenada na implantação da cultura do mirtilo - SILVA, Rômulo Eduardo Bernardes da (2018)
Nitrogen is a nutrient most required by blueberry, but there are few studies evaluating the response of the crop to fertilization. The objective of this work was to evaluate the initial growth of the blueberry crop as a function of nitrogen fertilization. The experiment was conducted in the field of Fruticulture of the Federal Institute of Minas Gerais - Campus of Muzambinho - MG. A randomized complete block design was used, with 6 treatments and 4 replications, totaling 24 plots. The treatments consisted of nitrogen doses: 0; 10; 20; 30; 40 and 50 g plant-1 of N, in the form of urea, divided in 3 applications at 30, 60 and 90 days after transplanting of the seedlings. The blueberry cultivar used was Climax, and the experiment was conducted for 266 days after transplanting. Plant height, stem diameter, number of branches, fresh matter and dry matter of leaves, stem, shoot (leaf + stem), roots, and chlorophyll and N content in leaves of plants . Nitrogen fertilization increases the initial growth of blueberry and N and chlorophyll content in the leaves of the crop; The dose of 20 g plant-1 of N is the most appropriate for blueberry cultivation in the first year after transplanting, in the southern region of Minas Gerais.